The Public-Private Distinction in Organization Theory: A Critique and Research Strategy - Perry, James L.; Rainey, Hal G. (Academy of Management Review, 1988)
Scholars have devoted increasing attention to similarities and differences between public and private organizations. This paper critiques the comparative literature on these organizations in order to assess the usefulness of the public-private distinction in organization theory and concludes that further analysis of this distinction is valuable. Several avenues for improving research are suggested, including clarification of the categories through an extension of previous conceptions, and assessment of a proposed typology of subcategories across the public-private continuum.